Extensibility of Hohenberg–Kohn Theorem to General Quantum Systems. Issue 10 (2nd August 2022) - Xu, Limin; Mao, Jiahao; Gao, Xingyu; Liu, Zheng
Abstract: The Hohenberg–Kohn (HK) theorem for interacting electrons is a cornerstone of modern electronic structure calculations. For a general quantum system, a HK‐type Hamiltonian in the form of H ̂ hk { g i } = H ̂ int + ∑ i g i O ̂ i $\hat {H}_{\rm hk}\lbrace g_i\rbrace =\hat {H}_{\rm int}+\sum_i g_i \hat O_i$ can always be defined, by grouping those terms with fixed or preknown coefficients into an internal part of the Hamiltonian H ̂ int $\hat {H}_{\rm int}$, and factorizing the remaining as the superposition of a set of Hermitian operators { O ̂ i } $\lbrace\hat {O}_i\rbrace$ . It is asked whether the HK theorem can be extended to such a general setting, so that the ground‐state expectation values of { O ̂ i } $\lbrace\hat {O}_i\rbrace$ as the generalized density can in principle be used as the fundamental variables determining all the properties of the system. It is shown that the question can be addressed by the invertibility of generalized density correlation matrix (GDCM) defined with respect to the { O ̂ i } $\lbrace\hat {O}_i\rbrace$ operators. This criterion is applied to several representative examples, including the quantum Ising dimer, frustration‐free systems, N ‐level quantum systems and a fermionic Hubbard chain. It is suggested that for a finite‐size system, finding an invertible GDCM under one single { g i } $\lbrace g_i\rbrace$ configuration is typically sufficient to establish the generic extensibility of the HK theorem in the entire parameter space. Abstract : The Hohenberg–Kohn theorem is a cornerstone of modern electronic structure computation. Here, it is aimed to expand its territory from interacting electrons to arbitrary quantum many body systems. By introducing the concept of generalized density correlation matrix, it is shown how the extensibility can be addressed in a mathematically rigorous and practically convenient way.